2007
DOI: 10.1007/s00213-007-0887-8
|View full text |Cite
|
Sign up to set email alerts
|

The scopolamine-reversal paradigm in rats and monkeys: the importance of computer-assisted operant-conditioning memory tasks for screening drug candidates

Abstract: Rationale The scopolamine-reversal model is enjoying a resurgence of interest in clinical studies as a reversible pharmacological model for Alzheimer's disease (AD). The cognitive impairment associated with scopolamine is similar to that in AD. The scopolamine model is not simply a cholinergic model, as it can be reversed by drugs that are noncholinergic cognition-enhancing agents. Objectives The objective of the study was to determine relevance of computer-assisted operant-conditioning tasks in the scopolamin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
37
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(42 citation statements)
references
References 55 publications
(63 reference statements)
5
37
0
Order By: Relevance
“…20) Furthermore, scopolamine-induced cognitive impairment is reversed by AChE inhibitors in animals, which is known to improve cognitive function in AD. 21) Consistent with other studies, we observed that the acute administration of scopolamine impaired fear-based contextual long-term memory in the passive avoidance test. 22) Furthermore, the scopolamine-induced memory impairments were reversed by the single administration of α-and β-amyrin.…”
Section: Discussionsupporting
confidence: 93%
“…20) Furthermore, scopolamine-induced cognitive impairment is reversed by AChE inhibitors in animals, which is known to improve cognitive function in AD. 21) Consistent with other studies, we observed that the acute administration of scopolamine impaired fear-based contextual long-term memory in the passive avoidance test. 22) Furthermore, the scopolamine-induced memory impairments were reversed by the single administration of α-and β-amyrin.…”
Section: Discussionsupporting
confidence: 93%
“…Donepezil treatment significantly improved PAL performance for the moderately difficult 3-3 trials but not for the easiest (2-2) or the most difficult (4-4) trials. This pattern is similar to the effects of donepezil seen in the NHP delayed match to sample task (Buccafusco et al, 2008) in which donepezil only improved scopolamine deficits at the small to moderate delays but not at the longer, most demanding delays. We believe that the lack of significant effect on the demanding (4-4) trials might simply be due to the smaller dynamic range between the scopolamine-and vehicletreated animals for those trials.…”
Section: Discussionsupporting
confidence: 73%
“…As a muscarinic receptor antagonist, scopolamine can impair learning and to some degree memory processing (Flood and Cherkin, 1986). Acute and systemic administration of scopolamine in young animals can offer a suitable substitute to the cholinergic deficit in AD and aging, and has been widely used in animal pharmacological models for the preliminary evaluation of potential cognitionenhancing agents (Buccafusco et al, 2007). Accordingly, in the present study, the scopolamine models had a worse performance in behavioral tests.…”
Section: Discussionmentioning
confidence: 93%